Asylum seekers in Brazil: time spent in migration status, their releases and weights on the current situation - Mortari A. C., Paulo; Martino, Andressa A. (Pontifícia Universidade Católica de São Paulo, 2020)
The “asylum seeker” category is defined as such as a consequence of the Refugee Status Determination (RSD) process. Nevertheless, what is supposed to be a transitory migratory stage at first may acquire nuances of permanence. In this article, we intend to come up with ways to assess the length of time asylum seekers remain under this migratory condition in Brazil nowadays, based on the CONARE’s (National Committee for Refugees) database, and evaluate some of the implications of such a scenario. We identify, among other results, a significant and sustainable increase in the time spent by migrants under the condition of asylum seeker from 2014 to 2020 when Venezuelans are not taken into account in the last two years, especially with regards to people who await three years or more a response to their applications. As part of the consequences, there are issues such as the lack of access to family reunion and difficulties in making practicable long-term plans due to uncertainties inherent to the migratory situation to which we refer. Finally, we offer a set of reflections on what seems to be an effort recently made by the government to reduce the backlog of asylum applications, with paramount attention to the migrants’ reality.